(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Single crystals of pure and Cdcl2 added sodium penta fluro antimonates, an electro optical crystal has been grown by slow evaporation technique. The grown crystals are subjected to single crystal X-ray diffraction, Fourier Transform Infrared(FTIR) studies, EDAX,UV-Vis studies and microhardness studies. Single crystal X-ray diffraction confirms that the crystal belongs to Orthorhombic system. The FTIR spectrum analysis has confirmed the functional groups in the grown crystal. The optical behaviour was examined by UV-Vis studies and found that the crystal is transparent in the entire visible region. Microhardness studies reveals the mechanical strength of the grown Crystal. The decomposition point of the sample was identified by TG/DTA studies. The samples was measured and Dielectric properties were measured at different frequencies and temperature.